2020
DOI: 10.1242/jcs.239004
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell reprogramming into repair cells increases miRNA-21 expression in exosomes promoting axonal growth

Abstract: Functional recovery after peripheral nerve damage is dependent on the reprogramming of differentiated Schwann cells (dSCs) into repair Schwann cells (rSCs), which promotes axonal regeneration and tissue homeostasis. Transition into a repair phenotype requires expression of c-Jun and Sox2, which transcriptionally mediates inhibition of the dSC program of myelination and activates a non-cellautonomous repair program, characterized by the secretion of neuronal survival and regenerative molecules, formation of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 69 publications
4
70
0
Order By: Relevance
“…In normal situation, the growth of DRGs and sensory neurons was enhanced by SKP-SC-EVs; additionally, after SKP-SC-EV treatment, OGDinjured neurons recovered the expression of functional protein GAP-43, neurite outgrowth, and cell viability. In agreement with this, EVs from SCs or other Schwann- [24,37,38]; moreover, Wang et al provided evidence that SC-exosomes have a therapeutic effect on diabetic peripheral neuropathy in mice and suggested that SC-exosomes' modulation of miRs contributes to this therapy [39]; especially, SCs reprogramming into repair cells can increase miR-21 expression in exosomes, promoting axonal growth [40]. In the same way, SC-like differentiated adipose stem cells could promote neurite outgrowth via secreted exosomes and RNA transfer [41].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In normal situation, the growth of DRGs and sensory neurons was enhanced by SKP-SC-EVs; additionally, after SKP-SC-EV treatment, OGDinjured neurons recovered the expression of functional protein GAP-43, neurite outgrowth, and cell viability. In agreement with this, EVs from SCs or other Schwann- [24,37,38]; moreover, Wang et al provided evidence that SC-exosomes have a therapeutic effect on diabetic peripheral neuropathy in mice and suggested that SC-exosomes' modulation of miRs contributes to this therapy [39]; especially, SCs reprogramming into repair cells can increase miR-21 expression in exosomes, promoting axonal growth [40]. In the same way, SC-like differentiated adipose stem cells could promote neurite outgrowth via secreted exosomes and RNA transfer [41].…”
Section: Discussionmentioning
confidence: 69%
“…In agreement with this, EVs from SCs or other Schwann-like cells have been evidenced as messenger for cell-to-cell communication, involved in neurite growth and regeneration process. SC-derived exosomes can mediate neuron-glia communication and enhance axonal regeneration through inducing the neuronal growth cone formation [ 24 , 37 , 38 ]; moreover, Wang et al provided evidence that SC-exosomes have a therapeutic effect on diabetic peripheral neuropathy in mice and suggested that SC-exosomes’ modulation of miRs contributes to this therapy [ 39 ]; especially, SCs reprogramming into repair cells can increase miR-21 expression in exosomes, promoting axonal growth [ 40 ]. In the same way, SC-like differentiated adipose stem cells could promote neurite outgrowth via secreted exosomes and RNA transfer [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of neuronal form and function by SCs has been found to be mediated by different forms of intercellular communication, including coupling via local currents in the periaxonal space, paracrine signaling (e.g., ATP, glutamate) and physical coupling via adhesion molecules and gap junctions [7]. In addition to these classic mechanisms, recent findings suggest the occurrence of lateral molecular cargo transfer mediated by secreted extracellular vesicles (EVs) from SCs to axons [8][9][10]. EVs constitute mainly two types of vesicles: exosomes and microvesicles, which are generated by all cell types and derive from multivesicular bodies or through bubbling of the plasma membrane, respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found recently that cultured SCs release particulate products in the form of extracellular vesicles or exosomes that are internalized by neurons. SC exosomes are stage-specific and promote axon regeneration in culture and after sciatic nerve injury [119].…”
Section: Promotion Of Neuronal Health and Axon Growthmentioning
confidence: 99%